A practical approach to establishing a critical care outreach service: An expert panel research design. Issue 1 (January 2023) - Williams, Ged; Pirret, Alison; Credland, Nicki; Odell, Mandy; Raftery, Chris; Smith, Duncan; Winterbottom, Fiona; Massey, Debbie
Abstract: Background: For over two decades, nurse-led critical care outreach services have improved the recognition, response, and management of deteriorating patients in general hospital wards, yet variation in terms, design, implementation, and evaluation of such services continue. For those establishing a critical care outreach service, these factors make the literature difficult to interpret and translate to the real-world setting. Aim: The aim of this study was to provide a practical approach to establishing a critical care outreach service in the hospital setting. Method: An international expert panel of clinicians, managers, and academics with experience in implementing, developing, operationalising, educating, and evaluating critical care outreach services collaborated to synthesise evidence, experience, and clinical judgment to develop a practical approach for those establishing a critical care outreach service. A rapid review of the literature identified publications relevant to the study. A modified Delphi technique was used to achieve expert panel consensus particularly in areas where insufficient published literature or ambiguities existed. Findings: There were 502 publications sourced from the rapid review, of which 104 were relevant and reviewed. Using the modified Delphi technique, the expert panel identified five key components needed to establish a critical care outreach service: (i) approaches to service delivery, (ii) education and training, (iii) organisational engagement, (iv) clinical governance, and (v) monitoring and evaluation. Conclusion: An expert panel research design successfully synthesised evidence, experience, and clinical judgement to provide a practical approach for those establishing a critical care outreach service. This method of research will likely be valuable in other areas of practice where terms are used interchangeably, and the literature is diverse and lacking a single approach to practice.